A modified carbon black adsorbent for adsorbing tetracycline and its preparation method and application
By treating conductive carbon black with oxalic acid and citric acid, increasing its pore size and oxygen-containing functional groups, the problem of difficulty in effectively removing tetracycline pollution in the water environment in the prior art is solved, and the effect of significantly improving the adsorption capacity of tetracycline is achieved.
Patent Information
- Application Number
- CN202410527581.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-29
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-04-29
AI Technical Summary
The prior art is difficult to effectively remove tetracycline pollution in the water environment, resulting in potential harm to aquatic organisms and ecosystems.
By placing the conductive carbon black in a mixture of oxalic acid and citric acid for pretreatment, the porosity, void ratio and surface oxygen-containing functional groups of the carbon black are increased, thereby improving its adsorption ability to tetracycline.
The adsorption capacity of modified carbon black adsorbent on tetracycline is improved. Compared with unmodified carbon black, the adsorption amount increases by 25.7%, and the adsorption effect in tetracycline solutions is significantly improved.
Smart Images

Figure CN118454645B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a modified carbon black adsorbent for adsorbing tetracycline, a preparation method and application thereof, and belongs to the technical field of functional materials and preparation thereof. Background Art
[0002] The upgrading of human economic activities has led to the discharge of a large number of compounds (including organic matter and antibiotics) into the aquatic environment, raising concerns about water quality and ecosystem integrity. It is worth noting that tetracycline antibiotics are a ubiquitous class of antibiotics that are widely present in pharmaceutical wastewater, causing pollution and potential harm to water bodies. These drugs are known for their broad antimicrobial spectrum and are widely used to treat human and livestock infections, in addition to being drugs that prevent and promote the growth of the latter. Due to the widespread use of tetracycline in the medical field, its release has continued to increase, resulting in a gradual increase in its environmental concentration, which has an adverse effect on aquatic organisms and ecosystems. The excessive presence of tetracycline can lead to the destruction of the balance of the ecological chain and water system, and may even lead to the emergence of antibiotic-resistant bacteria, thereby exacerbating the problem of water pollution. Therefore, seeking effective and economically feasible methods to eliminate tetracycline from the aquatic environment has become a contemporary priority.
[0003] In recent years, scholars have demonstrated that carbon black has a considerable adsorption capacity for tetracycline, and revealed that the porous structure of carbon black and its rich functional groups produce a strong adsorption interaction with tetracycline molecules, thereby promoting the efficient extraction of tetracycline from water environments. At the same time, the potential of various carbon black materials to enhance adsorption efficiency has been emphasized, thereby expanding the scope of application of carbon black in tetracycline-contaminated water remediation. In addition, the research of other researchers has emphasized the enhancement of carbon black's adsorption properties through surface modification, thus providing an innovative approach to refining carbon black adsorption technology.
[0004] However, different modified carbon blacks have different physical and chemical properties such as pore structure, density, specific surface area, pH, cation exchange capacity, oxygen-containing functional groups, etc. due to different preparation raw materials, pyrolysis technology and pyrolysis conditions. These physical and chemical properties also have different adsorption performance for organic pollutants. Therefore, it is very necessary to provide a modified carbon black adsorbent that can be used for efficient adsorption of tetracycline. Summary of the invention
[0005] The object of the present invention is to provide a modified carbon black adsorbent which can be used for efficiently adsorbing tetracycline.
[0006] The technical solution of the present invention:
[0007] One of the objects of the present invention is to provide a method for preparing a modified carbon black adsorbent, the method comprising the following steps:
[0008] (1) After pretreatment, the conductive carbon black is placed in a mixture of oxalic acid and citric acid and allowed to stand at room temperature for 20 to 24 hours;
[0009] (2) After the soaking is completed, take out the carbon black and dry it;
[0010] (3) After drying, the product is washed until the washing liquid is neutral, dried again, ground, and sieved to obtain modified carbon black.
[0011] It is further defined that the pretreatment process of the conductive carbon black in (1) is: washing three times with distilled water as the washing liquid, drying in an oven for 2-4 hours after washing, and crushing through a 100-mesh sieve after drying to obtain pretreated carbon black.
[0012] It is further defined that the molar ratio of oxalic acid to citric acid in the mixed solution of oxalic acid and citric acid in (1) is 2:1.
[0013] It is further defined that in (1), the concentration of oxalic acid in the mixed solution of oxalic acid and citric acid is 0.2-1 mol / L, and the concentration of citric acid is 0.1-0.5 mol / L.
[0014] It is further defined that the drying temperature in (2) is 100-105°C and the drying time is 10-12 hours.
[0015] It is further specified that in (3), distilled water is used as the washing liquid.
[0016] It is further defined that the re-drying temperature in (3) is 105°C.
[0017] Further defined, (3) passing through a 100 mesh sieve.
[0018] The second object of the present invention is to provide an application of the modified carbon black adsorbent prepared by the above method, specifically for adsorbing tetracycline in wastewater.
[0019] Beneficial effects:
[0020] The present invention uses oxalic acid and citric acid to treat carbon black, effectively increasing the pore size and porosity of carbon black, while effectively increasing the oxygen-containing functional groups on the surface of carbon black, so that the adsorption capacity of carbon black for tetracycline is improved. In addition, the graphite layer does exist in the carbon black structure, which can also increase the adsorption of tetracycline. Compared with the prior art, the present application has the following advantages:
[0021] (1) The present invention uses a mixture of organic acids oxalic acid and citric acid to treat carbon black, and the generated oxygen-containing functional groups are more than those generated by its modifier, and both high molecular weight citric acid and low molecular weight oxalic acid are attached to the surface of carbon black, so that the adsorption capacity of carbon black is further improved.
[0022] (2) The presence of a graphite layer in the conductive carbon black structure used in the present invention can increase the adsorption of tetracycline. In addition, commercial carbon black contains polycyclic aromatic hydrocarbons due to production reasons. The aromatic ring π electrons of the polycyclic aromatic hydrocarbons have a π-π dispersion effect on tetracycline, so that tetracycline is adsorbed on the carbon black. The hydrogen bonding between the carbon black and tetracycline is also conducive to the adsorption between the two.
[0023] (3) The modified carbon black adsorbent prepared by the present invention has a carbon black adsorbent of 1132.6 m 2 / g of specific surface area, and its adsorption capacity for tetracycline solution with a concentration of 250 mg / L is 436 mg / g, which is 25.7% higher than the adsorption capacity of unmodified carbon black of 324 mg / g. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a scanning electron microscope image of the modified carbon black adsorbent prepared in Example 1;
[0025] Figure 2 This is the infrared spectrum of the modified carbon black adsorbent prepared in Example 1;
[0026] Figure 3 It is a comparison chart of the adsorption amount of tetracycline by the adsorbent prepared in Example 1 and Comparative Examples 1 to 4;
[0027] Figure 4 The adsorption amount of tetracycline of different concentrations by the modified carbon black adsorbent prepared in Example 1;
[0028] Figure 5 This is a comparison chart of the adsorption capacity of tetracycline by the adsorbent prepared in comparative example 0.5 mol / L. DETAILED DESCRIPTION
[0029] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0030] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0031] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0032] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.
[0033] The conductive carbon black used in the following examples and comparative examples was purchased from Kain Corporation, model number AC30.
[0034] Ordinary carbon black was purchased from Chenqi Chemical Co., Ltd., model number VXC72.
[0035] Example 1
[0036] (1) Pretreatment: Conductive carbon black was used as raw material, washed with distilled water, dried in an oven for 2 h, and crushed to pass through a 100-mesh sieve; 0.4 mol of oxalic acid and 0.2 mol of citric acid were placed in 1 L of water and mixed evenly to obtain a modifier; 3 g of the pretreated conductive carbon black was immersed in 180 mL of the modifier, allowed to stand at room temperature for 24 h, and then dried at 100-105 °C for 12 h.
[0037] (2) Cleaning: The carbon black after drying is cleaned to neutrality, and then dried at 105°C and ground through a 100-mesh sieve to obtain a modified carbon black adsorbent.
[0038] The scanning electron microscope image of the modified carbon black adsorbent prepared in this example is as follows: Figure 1 As shown, the surface is rough and the pores are rich.
[0039] The specific surface area and pore size of the modified carbon black adsorbent and their proportions were determined by the BET specific surface area test method. The test results are shown in Table 1:
[0040] Table 1
[0041]
[0042]
[0043] It can be seen from the above table that the specific surface area of the modified carbon black adsorbent prepared in this embodiment is 1132.6 m2 / g.
[0044] Comparative Example 1
[0045] The difference between this comparative example and Example 1 is that ordinary carbon black is used to replace conductive carbon black, and the remaining process steps and parameter settings are the same as those in Example 1.
[0046] The pore structure of the modified carbon black adsorbent prepared in this comparative example is not as rich as that in Example 1, and its specific surface area is 323.25 m 2 / g, which is much lower than the modified carbon black adsorbent prepared in Example 1. The main reason for this difference is that the conductive carbon black and ordinary carbon black have different structures, and their specific surface areas and pore sizes are very different. The conductive carbon black used in Example 1 has great adaptability to the mixed solution of oxalic acid and citric acid, so the specific surface areas of the two are quite different.
[0047] Comparative Example 2
[0048] The difference between this comparative example and Example 1 is that the preparation of the modifier is as follows: 200 mL of concentrated nitric acid solution with a mass concentration of 65% is added to 100 mL of water, and the remaining process steps and parameter settings are the same as those in Example 1.
[0049] In this comparative example, due to the strong corrosiveness of concentrated nitric acid, it caused severe etching of the conductive carbon black, resulting in partial collapse of the pore size in the carbon black and a reduction in the specific surface area to 768.64 m 2 / g.
[0050] Comparative Example 3
[0051] The difference between this comparative example and Example 1 is that the oxalic acid is 0.2 mol and the citric acid is 0.4 mol (the molar ratio of oxalic acid to citric acid is 1:2), and the remaining process steps and parameter settings are the same as those in Example 1.
[0052] Comparative Example 4
[0053] The difference between this comparative example and Example 1 is that the oxalic acid is 0.3 mol and the citric acid is 0.3 mol (the molar ratio of oxalic acid to citric acid is 1:1), and the remaining process steps and parameter settings are the same as those in Example 1.
[0054] Effect example
[0055] (1) The pH of a tetracycline solution with a concentration of 250 mg / L was adjusted to between 7.5 and 8.5, and then the adsorbents prepared in Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 were added at a ratio of 10 mg of adsorbent per 20 mL of tetracycline solution. The mixture was shaken at 250 rpm for 4 h, and then filtered through a 0.45 μm water filter membrane. The tetracycline concentration in the solution was determined by ultraviolet spectrophotometry. The equilibrium adsorption amount of each adsorbent was calculated based on the change in tetracycline concentration before and after adsorption. The results are shown in FIG. Figure 3 As shown. Figure 3 It can be seen that the adsorbents prepared in Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 have adsorption amounts of tetracycline of 436 mg / g, 168 mg / g, 362 mg / g, 394 mg / g and 418 mg / g, respectively.
[0056] (2) The concentration of tetracycline was adjusted to 200 mg / g, 250 mg / g, 300 mg / g, 350 mg / g and 400 mg / g. The adsorbent prepared in Example 1 was used for testing. The mixture was shaken at 250 rpm for 4 h and then filtered through a 0.45 μm water filter. The tetracycline concentration in the solution was determined by ultraviolet spectrophotometry. The equilibrium adsorption capacity of each adsorbent was calculated based on the change in tetracycline concentration before and after adsorption. The results are shown in FIG. Figure 4 As shown by Figure 4 It can be seen that when the concentration of tetracycline is 200 mg / g, 250 mg / g, 300 mg / g, 350 mg / g and 400 mg / g respectively, the adsorption amount of tetracycline by the adsorbent prepared in Example 1 is 398 mg / g, 436 mg / g, 438 mg / g, 439 mg / g and 442 mg / g respectively.
[0057] Comparative Example 5
[0058] The difference between this comparative example and Example 1 is that 0.5 mol / L oxalic acid, 0.5 mol / L acetic acid, 0.5 mol / L citric acid and 0.5 mol / L tartaric acid are used as modifiers to treat the conductive carbon black, and the remaining process steps and parameter settings are the same as those in Example 1.
[0059] The pH of a tetracycline solution with a concentration of 250 mg / L was adjusted to between 7.5 and 8.5, and then the above four adsorbents and original carbon black (conductive carbon black) were added respectively according to the ratio of adding 10 mg of adsorbent to every 20 mL of tetracycline solution. The mixture was shaken at 250 rpm for 4 hours, and then filtered through a 0.45 μm water filter membrane. The tetracycline concentration in the solution was determined by ultraviolet spectrophotometry. The equilibrium adsorption capacity of each adsorbent was calculated based on the change in tetracycline concentration before and after adsorption. The results are shown in FIG. Figure 5 As shown. Figure 5 It can be seen that the adsorption performance of the modified carbon black adsorbent prepared by using low molecular weight organic acids oxalic acid, acetic acid, citric acid and tartaric acid as modifiers for tetracycline is slightly improved compared with the adsorption performance of the original carbon black (conductive carbon black). After adding 0.5 mol / L acetic acid solution for modification, the modified carbon black adsorbent prepared by the modification treatment according to the method of the present invention has enhanced adsorption capacity for tetracycline, but compared with the modified carbon black adsorbent obtained by co-modification with oxalic acid and citric acid in Example 1, the improvement effect is small.
[0060] Although the present invention has been disclosed as above in the preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A method for preparing a modified carbon black adsorbent, characterized in that: include: (1) After pretreatment, the conductive carbon black is placed in a mixture of oxalic acid and citric acid and allowed to stand at room temperature for 20 to 24 hours; In the mixed solution of oxalic acid and citric acid in (1), the concentration of oxalic acid is 0.2-1 mol / L, and the concentration of citric acid is 0.1-0.5 mol / L; the molar ratio of oxalic acid to citric acid is 2:1; (2) After the soaking is completed, take out the carbon black and dry it; (3) After drying, the product is washed until the washing liquid is neutral, dried again, ground, and sieved to obtain modified carbon black.
2. The preparation method according to claim 1, characterized in that: (1) The pretreatment process of conductive carbon black is as follows: using distilled water as washing liquid, washing 3 times, drying in an oven for 2-4 hours after washing, and crushing through a 100-mesh sieve after drying to obtain pretreated carbon black.
3. The preparation method according to claim 1, characterized in that: (2) The drying temperature is 100-105°C and the drying time is 10-12 hours.
4. The preparation method according to claim 1, characterized in that: (3) Distilled water was used as the washing liquid.
5. The preparation method according to claim 1, characterized in that: The secondary drying temperature in (3) is 105°C.
6. The preparation method according to claim 1, characterized in that: (3) Pass through a 100-mesh sieve.
7. A modified carbon black adsorbent prepared by the method according to any one of claims 1 to 6.
8. An application of the modified carbon black adsorbent according to claim 7, characterized in that: Used to adsorb tetracycline in wastewater.
Citation Information
Patent Citations
Polyester fiber filter material for biological filter as well as preparation method and modification method of polyester fiber filter material
CN116716677A